Konseling Kognitif Dengan Teknik Reframing Pikiran Untuk Meningkatkan Self-Intraception - Nasution, Noviari P; Gading, I Ketut (Department of Guidance and Counseling, FIP, Undiksha, 2018)
This study aims to determine the effectiveness of cognitive counseling techniques reframing the mind to improve the self-intraception of high school students Lab. Undiksha Singaraja. The population of this study is all students of class XI SMA Lab.Undiksha. The sample of this research is determined by purposive sampling technique with 7 student. Methods of data collection in research using interview method, diary, and questionnaire self intraception pattern likert scale. Data analysis method for hypothesis test using t-test. The results of this study indicate that cognitive counseling techniques reframing the mind effectively to increase the intraception of students of class XI SMA Lab.Undiksha.